Histological Study on the Nasal Cavity of Black Iraqi Goat (Capra hircus) - A.R., Mustafa; Reshag, Ali F. (The Iraqi Journal of Veterinary Medicine, 2019)
The histological observations of this study which conducted on nasal cavity of black Iraqi goat revealed that the nasal cavity consisted of three regions (vestibular, respiratory and olfactory(.The vestibular region was narrow zone, lined with (non keratinized) stratified squamous epithelium, and its propria submucosa contained serous glands and blood vessels.The respiratory region was lined with ciliated pseudostratified columnar epithelia with goblet cells. The vascular propria submucosa had mucous glands, which were positive to periodic acdic shieff and Alcian blue stains. The olfactory region was lined with thick pseudostratified columnar epithelium devoid of goblet cells and contained, the propria submucosa serous simple acinus Alcian positive glands (Bowman’s glands) and numerous nerve bundles. The histological results concluded that the nasal cavity of black Iraqi goat was good adaptive tooled for hot dusty environment.